Soil magnetic signature for identification of areas with different sorption potentials of imazaquin - Peluco, Rafael Gonçalves [UNESP]; Marques Júnior, José [UNESP]; Siqueira, Diego Silva [UNESP]; Silva, Laércio Santos [UNESP]; Gomes, Romário Pimenta [UNESP] (Elsevier, 2020)
It is imperative that the increase in world agricultural production be carried out in a sustainable way, minimizing negative environmental effects caused, among other reasons, by herbicide use. This study aimed to assess the potential of using soil magnetic signature to identify areas with different sorption capacities of the herbicide imazaquin. A total of 374 soil samples were collected at a depth of 0.0–0.25 m from a grid with sampling density of 1 point every 2.4 ha in an area of 908 ha for determining the organic matter, pH, dithionite and oxalate iron contents, clay content, Freundlich sorption coefficient of the herbicide imazaquin, and magnetic susceptibility (MS). The results were submitted to descriptive statistics and Pearson correlation analysis. Regression models were constructed to estimate the Freundlich sorption coefficient of the herbicide imazaquin from MS. The spatial dependence was assessed by geostatistical analysis and spatial pattern maps and cross-variograms were constructed. MS allows an indirect quantification of imazaquin sorption. Soils with higher magnetic expression have higher sorption potential of imazaquin. Soil magnetic signature can assist in mapping and identifying areas with different potentials of herbicide application.
Keywords: Geostatistics; Herbicide; Magnetic susceptibility; Pedotransfer